Compost Quality of Compost Process Grass Waste with Composting Bin Method - Vivin Setiani; Ayu Nindyapuspa; Rizki Alifiya Nurbiyanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
The increasing of organic waste can increase environmental pollution. This can be overcome by doing aerobic composting of organic waste. This was because the method includes a simple composting method in its application. The aim of this study is to analyze the quality of compost from grass waste. In this study, composting of grass waste, banana leaf waste and cotton waste has been carried out aerobically with the waste composting method. The compost material consisted of 76% grass waste, 12% banana leaf waste and 12% cotton waste with the addition of EM4 0, 10 and 50 mL/Kg doses of compost material. Monitoring of quality compost consist of temperature, pH, moisture content, C/N ratio, phosphor and potassium. Analysis of compost quality in this study refers to SNI 19-7030-2004. The results showed that the quality of compost without the addition of EM4 was the best compost quality of all the variables in this study.